EGGS, LARVAE AND JUVENILES OF THE INDIAN SPRAT, SARDINELLA JUSSIEU (LACEPEDE) - Bensam, P (Indian Journal of Fisheries, 2011)
Sardinella jussieu = Sardinella gibbosa (Bleeker), popularly known as theIndian sprat, is one of the commercially important sardines occurring inIndian coastal waters. No adequate information is available hitherto onthe early development of this fish although work- was in progress on someaspects of its fishery and biology (Devanesan, 1932; Chacko, 194(5, 1950;Sekharan, 1955, 1959; Ganapati and Rao, %1957; Dharmamba, 1959;Bennet, 1961; Dutt, 1961). While examining the plankton collected offCannanore, south-west coast of India (surface hauls from the 6-fathom stationsampled by a | metre net of fine organdie cloth), during January-May1964, a search for the eggs and larvae of S. jussieu was made because partlyand fully spawned specimens appeared in large numbers in the local catchesof both indigenous crafts and mechanised vessels.